Inexpensive gram scale synthesis of porous Ti4O7 for high performance polymer electrolyte fuel cell electrodes. Issue 95 (17th November 2021) - Chisaka, Mitsuharu; Nagano, Waka; Delgertsetseg, Byambasuren; Takeguchi, Tatsuya
Abstract : More than 2 grams of porous Ti4 O7 supports for high performance fuel cell electrodes were synthesized in a single reaction by simply increasing the precursor mass used in the developed inexpensive route. Abstract : As a fuel cell catalyst support, more than 2 g of Magnéli phase Ti4 O7 fine-particles were synthesized in a single reaction via an inexpensive route. The single-cell performance reached that of commercial carbon-supported platinum, with an excellent load cycle durability, one of the highest ever reported for oxide-supported platinum catalysts.